SPE and determination by FAAS of heavy metals using a new synthesized polymer resin in various water and dried vegetables samples - Dasbasi, Teslima; Muglu, Halit; Soykan, Cengiz; Ulgen, Ahmet (Informa UK Limited, 2018)
Firstly, poly[phenyl thiadiazole methacrylamide-co-divinylbenzene-co-2-acrylamido-2-methylpropane sulfonic acid] (PTMAAm-co-DVB-co-AMPS), a new polymer resin was synthesized. This polymer resin was...
Keywords: Heavy metals; Phenyl thiadiazole methacrylamide; FAAS; Synthesized polymer; Solid phase extraction